2018
DOI: 10.1101/294306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Candidate Gene Networks for Acylsugar Metabolism and Plant Defense in Wild TomatoSolanum pennellii

Abstract: 1Many plants in the Solanaceae family secrete acylsugars, which are branched-chain and straight-2 chain fatty acids esterified to glucose or sucrose. These compounds have important roles in plant 3 defense and potential commercial applications. However, several acylsugar metabolic genes 4 remain unidentified, and little is known about regulation of this pathway. We used comparative 5 transcriptomic analysis between low-and high-acylsugar-producing accessions of Solanum 6 pennellii and found that expression lev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 71 publications
(142 reference statements)
0
22
0
Order By: Relevance
“…A group of accessions from the Nazca region, described as S. pennellii var. puberulum , are trichome-deficient and exhibit the minimal accumulation of acylsugars and transcripts of genes associated with acylsugar metabolism [ 26 , 39 ]; our pilot experiments confirmed the absence of detectable acylsugars in this group and these accessions were excluded from this study. All extracts were analyzed by UHPLC–HR-MS using positive-mode electrospray ionization.…”
Section: Resultsmentioning
confidence: 77%
“…A group of accessions from the Nazca region, described as S. pennellii var. puberulum , are trichome-deficient and exhibit the minimal accumulation of acylsugars and transcripts of genes associated with acylsugar metabolism [ 26 , 39 ]; our pilot experiments confirmed the absence of detectable acylsugars in this group and these accessions were excluded from this study. All extracts were analyzed by UHPLC–HR-MS using positive-mode electrospray ionization.…”
Section: Resultsmentioning
confidence: 77%
“…S. pennellii natural accessions ( Mandal et al, 2020 ), as well as the S. lycopersicum M82 × S. pennellii LA0716 chromosomal substitution introgression lines (ILs) ( Eshed and Zamir, 1995 ), offer convenient resources to investigate interspecific genetic variation that affects acylsugar metabolic diversity ( Mandal et al, 2020 ; Schilmiller et al, 2010 ). In a rescreen of ILs for S. pennellii genetic regions that alter trichome acylsugar profiles ( Schilmiller et al, 2010 ), IL7-4 was found to accumulate increased C10 medium chain containing acylsugars compared with M82 ( Figure 2 , A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Together, these steps resulted in a list of 42 candidates. Previously characterized ASATs are expressed and enriched in glandular trichomes relative to non-acylsugar-accumulating tissues (Schilmiller et al, 2012a; Ning et al, 2015; Fan et al, 2016; Moghe et al, 2017;Nadakuduti et al, 2017;Leong et al, 2019;Mandal et al, 2020). Thus, the 17 candidates with more than 500 reads in the trichome samples were selected for further analysis.…”
Section: Identification Of Acylinositol Acyltransferase Candidates Inmentioning
confidence: 99%
“…ASATs sequentially transfer acyl chains from acyl-CoAs to generate acylsucroses in plants as phylogenetically divergent as cultivated tomato (Solanum lycopersicum), Solanum pennellii, Petunia axillaris, and Salpiglossis sinuata (Schilmiller et al, 2012a(Schilmiller et al, , 2015Fan et al, 2016Fan et al, , 2017Moghe et al, 2017;Nadakuduti et al, 2017). The expression of characterized ASATs is enriched in glandular trichomes relative to non-acylsugar-producing tissues (Ning et al, 2015;Moghe et al, 2017;Nadakuduti et al, 2017;Leong et al, 2019;Mandal et al, 2020). Phylogenetic and functional analyses revealed that orthologs have similar, but distinct, substrate selectivity in acylsugar biosynthesis across the Solanaceae family (Moghe et al, 2017;Nadakuduti et al, 2017).…”
mentioning
confidence: 99%